The Symptoms and Causes of Schizophrenia Perceived by Indonesian People with Schizophrenia: A Phenomenology Study (International Journal of Nursing Education, 2022)
Many people with schizophrenia are unaware that they have a mental illness. They frequently havetrouble detecting their illness symptoms and recognizing the presence of a mental disorder and, moresignificantly, that they require long-term treatment and care. This has the unintended consequenceof causing a poor outcome. This study aims to explore the experiences of symptoms and causes ofschizophrenia of Indonesian people with schizophrenia. This study uses a qualitative method witha phenomenological approach. Participants in this study were patients with schizophrenia in AcehProvince, Indonesia. The results of this study identified two themes: confusion over symptoms’ natureand severity and out-of-control things that cause schizophrenia. The results of this study found that themajority of people with schizophrenia struggle to understand the severity of their symptoms. Some oftheir ideas about the reasons for their illness indicate that health professionals should provide morethorough education about their illness.